(3GdTeS GdefjQI GdRgQGA aj JMbjb HMK eG CONdg GdcaGQ OGQge bgQkG heG jJUd ef aQGFO GdahGFOs - (3GdMSjf Hf fGUQ Hf YHO GdMajX Hf YHO Gddg GdegdG,J (B1111 (3g` s
(3ChdgG (B:s
(3jbhd GdabjQ GHf GdegdG GdMeO ddg GdPi TQa GdESdGe , hYQa SHd GdMdGd hGdMQGe hHYO aEfg hQO EdjfG SDGd cQje TGgO dUGMHg GdgGOi Hf C;eO GdLdG hgh Cf CUMGHfG GdRjOjI CUdhG Cf GdcaGQ s
(3BNQgG (B:s
(3hbO CKHJ ef GdLhGH Ydi eG PcQg GdSjO ai caGQ GdJChjd ef cdGe GdeJhcd Ydi Gddg eG ajg caGjI ddWGdHjf GdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3HBNQgG cdGe ddMSf Hf GdMSjf Hf CejQ GdeDefjf cJHg deG hba Ydi gPg GdeNWhWI s
(3hcPdc HBNQg aGFOI efbhdI ef TQM GdaUhd s
(3Ydi WQJgG Jedc HGSe CMeO Hf jMji s
Keywords: (3Gdabg GdESdGejs